Double check discharge planning to improve the results of a heart failure programme. (25th November 2020) - Alcoberro, L; Vime, J; Enjuanes, C; Jimenez, S; Garay, A; Yun, S; Moliner, P; Guerrero, C; Hidalgo, E; Calero, E; Marin, R; Alcober, L; et al.
Abstract: Background: Reduction of readmissions in heart failure (HF) patients is a main goal of HF programmes. Establishing a discharge planning for the patient and coordinating it with primary care teams are key aspects for their success. Purpose: Evaluate whether a double check discharge planning based on adding face-to-face joint weekly sessions with primary care managers to the conventional electronic communication of care plan reduces 6-month readmission and 6-month mortality. Methods: We evaluated all patients discharged from hospital with HF as primary diagnosis between September 2017 and January 2019. We compared outcomes between patients discharged during Period #1 (single check; September 2017 - April 2018) and those discharged during Period #2 (double check; May 2018 - January 2019). Primary endpoint was the combined endpoint of all-cause death or all-cause hospitalization 6 months after discharge from the index hospitalization. Results: The study enrolled 317 patients: 182 in Period #1 and 135 in Period #2. Mean age was 76±9 years. There was a higher proportion of patients with diabetes and COPD in Period #1, with no differences in other baseline characteristics. The combined endpoint of all cause-death and all-cause hospitalization at 6 months was significantly reduced in patients in the double check discharge planning group (27% vs. 16%, p 0.021). Conclusions: In a HF programme, the addition of a double check discharge planning based on having joint weekly sessions with primary care managers on top of the conventional electronic communication of care plan reduces 6-month readmission and 6-month mortality. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Hospital Universitari de Bellvitge